MASALAH BANJIR SEBAGAI AKIBAT DARI BURUKNYA SISTEM PENGELOLAAN DAS: STUDI KASUS DI DAS CANTIGA BINTARO - Rahardjo, Petrus Nugro (Jurnal Hidrosfir Indonesia, 2009)
Management of a catchment area should be done properly. For an example, there is no doubt a big mistake has already been done by the local government of DKI Jakarta in managing the 3 catchment areas, such as Ciliwung, Citarum and Cisadane. The management of the three catchment areas is coordinated by DKI Jakarta, together with Province West Java and Banten. The local governments do not have a consistency in planning and developing their region, especially for the supporting regions located in theupstream area. The effect is a big flood happened in Jakarta on the first February 2008. For the small catchment area, such as Cantiga, it is a good example to be discussed. The catchment area is located in district Pondok Aren. Flooding continuously happens every rainy season. The seven causes are no sustainable development program, no cleanly way of life, no good drainage system, unconsistency on regional planning and development program, no intensive conservation program, land subsidence and very high amount of rainfall. To cope with the flood problem and to carry out the flood control action, many consistently applied programs have to be done, ie. sustainable development, mopping up way of life, water front village concept implementation, one river one management concept implementation, artificialrecharge ponds and ground water injection.